QR Code-Based Attendance Systems in Education: A Systematic Literature Review on Data Accuracy and Sustainable School Management - Jodi Hendrawan; Perwitasari, Ika Devi; Fajar Maulana (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to evaluate the effectiveness of QR Code-based attendance systems in enhancing data accuracy and supporting sustainable school management. A Systematic Literature Review (SLR) was conducted using the PRISMA framework to analyze 9 selected articles published between 2015 and 2025. The review process involved identification, screening, eligibility assessment, and inclusion, with data extracted regarding research objectives, methods, respondents, applied technologies, and findings. The results indicate four major themes. First, efficiency was the most consistent advantage, as QR Code systems significantly reduced the time required for attendance and minimized administrative workload. Second, accuracy and reliability improved through automated digital records, reducing human errors and enabling evidence-based decision-making in educational institutions. Third, security was enhanced with innovations such as randomized QR, animated QR, and dynamic QR codes integrated with geofencing and IMEI validation, effectively preventing fraudulent practices like proxy attendance and buddy punching. Fourth, QR Code attendance systems demonstrated clear contributions to sustainable school management, particularly through integration with academic and financial systems, thereby promoting transparency and institutional accountability. This review concludes that QR Code-based attendance systems represent a simple yet strategic innovation with significant academic and managerial implications. Future research should focus on comparative studies across different QR Code models, long-term evaluations, and wider applications in primary and secondary schools to further strengthen digital transformation in education.